2016
DOI: 10.1523/jneurosci.3300-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neural Variability in Premotor, Motor, and Posterior Parietal Cortex during Change of Motor Intention

Abstract: The time course of neural variability was studied in three nodes of the parieto-frontal system: the dorsal premotor cortex (PMd, area 6), primary motor cortex (MI, area 4), and posterior parietal cortex (PPC, area 5) while monkeys made either direct reaches to visual targets or changed reach direction in response to an unexpected change of target location. These areas are crucial nodes in the distributed control of reaching and their lesion impairs trajectory formation and correction under different circumstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The second view is that neuronal variability is not entirely noise, rather it may also contain uncontrolled internal variables influenced by attention or intent, because the observed noise seems to be correlated within the recorded population (measured as noise correlation; Lee et al, 1998 ; Churchland et al, 2010 ; Marcos et al, 2013 ; Lin et al, 2015 ). A series of studies also suggested that neuronal variability can be beneficial for boosting weak signals (Stacey and Durand, 2001 ) or serving as modulatory signals (Lee et al, 1998 ; Boerlin and Deneve, 2011 ; Kohn et al, 2016 ; Saberi-Moghadam et al, 2016 ).…”
Section: Does Neuronal Variability Reflect Noise or Something Else?mentioning
confidence: 99%
“…The second view is that neuronal variability is not entirely noise, rather it may also contain uncontrolled internal variables influenced by attention or intent, because the observed noise seems to be correlated within the recorded population (measured as noise correlation; Lee et al, 1998 ; Churchland et al, 2010 ; Marcos et al, 2013 ; Lin et al, 2015 ). A series of studies also suggested that neuronal variability can be beneficial for boosting weak signals (Stacey and Durand, 2001 ) or serving as modulatory signals (Lee et al, 1998 ; Boerlin and Deneve, 2011 ; Kohn et al, 2016 ; Saberi-Moghadam et al, 2016 ).…”
Section: Does Neuronal Variability Reflect Noise or Something Else?mentioning
confidence: 99%
“…Whenever a motor action is performed repeatedly, there is inherent variability in the kinematics and the outcome of each movement [25,26]. This variability can arise from noise or other subtle differences in neural and muscle activity [27][28][29][30][31][32][33] that can occur both during movement preparation [34][35][36][37] and execution [37][38][39]. Movement variability is sensitive to the sensorimotor and timing demands of a task.…”
Section: Introductionmentioning
confidence: 99%
“…For example, shell left high gamma power begins to approach its feeding level of activity before feeding initiates, stabilizes during feeding, and returns toward Not-Feeding levels after feeding stops. In other cases there is a pattern of decreased variance around feeding which has been seen in the literature in response to visual stimuli and rewards [52], as a marker of stimulus perception/detection [53,54], been correlated with behavioral performance [55,56] and motor preparation/initiation [57,58]. When the timing of the ramping events across the different LFP features is considered, it is apparent that they occur on different timescales.…”
Section: Number Of Predictors Required For Stable Performancementioning
confidence: 83%
“…Given that motor initiation and preparation are known to manifest as decreased neural variability [57,58] there is a possibility that the decrease in LFP signal variance around feeding was merely a byproduct of the approach behavior of the animal. It is also possible that the success of our pre-feeding models was really detecting approach behavior.…”
Section: Confounds and Noisementioning
confidence: 99%